Assessment of farm accountancy data network system in Croatia - Juračak, Josip (Array, 2021)
Croatia is the newest member of the EU Farm Accountancy Data Network (FADN). So far, no comprehensive evaluation of the national FADN system has been conducted, and this study based on a survey of staff involved and a desktop analysis was conducted to fill this gap. The three main elements of the Croatian FADN system are the National FADN Committee, the Ministry of Agriculture as Liaison Agency (LA) and the Croatian Bureau for statistics. All FADN survey activities are carried out by LA and the main burden of data collection lies with the data collectors and the farms. The system operates in accordance with relevant EU legislation and currently its main objective appears to be the fulfilment of its obligations to the FADN network. Other benefits like analysis of CAP measures etc. are not yet exploited. The main challenges are further development of quality assurance systems, the motivation of staff and farms to participate, the increased use of FADN data, and the expected changes in transformation of the FADN into the sustainability data network (FSDN). Croatia will successfully meet these challenges if it strengthens its capacity for FADN research and data analysis and establishes an effective quality assurance system.